CLUSTERING TECHNIQUE AND VOCABULARY MASTERY TOWARDS STUDENTS’ WRITING SKILL IN RECOUNT TEXT - Nurfitria Ambarwati; Gustaman Saragih (Universitas Indraprasta PGRI, 2021)
Abstract: The purpose of this research at finding out empirical evidence concerning whether clustering technique and vocabulary mastery are effective or not for the student to write recount text. The research methodology used is an experiment. The sampling technique uses random sampling at Private Vocational High Schools in East Jakarta. Data collection is obtained by testing their vocabulary mastery and writing skills. Data analysis to test hypothesis is two ways ANOVA. The research results conclude 1) There is a significant effect of the clustering technique on students’ writing skills with the value (Sig) being 0.000 < 0.05 and F0 = 36.740. 2) A significant effect of vocabulary mastery on students’ writing skills with the value (Sig) is 0.000 < 0.05 and F0 = 72.161. 3) There is a significant interactive effect of clustering technique and vocabulary mastery on students’ writing skills. With the value (sig) is 0.018 < 0.05 and F0 = 5.921. Then all of H0 is rejected, and H1 is accepted. So, there is the effect of clustering technique and vocabulary mastery on students’ writing skills in recount text.Keywords: Clustering Technique, Vocabulary Mastery, Writing Skill, Recount Text